Flag Leaf Photosynthesis and Stomatal Function of Grain Sorghum as Influenced by Changing Photosynthetic Photon Flux Densities - H. Arnold Bruns (International Journal of Agronomy)
Photosynthesis (A) and stomatal function research in grain sorghum (Sorghum bicolor (L.) Moench) is limited compared to other crops. Flag leaves from three plants of two hybrids, grown with added N-fertilizer of 0.0, 112, and 224 kg ha−1 near Elizabeth, MS, were measured for A and stomatal functions at growth stages GS6 and GS7. A Li-Cor LI-6400XT set at 355 µmol [CO2], a flow rate of 500 µmol s−1, and a 6400-02 LED light source were used to collect data. Light levels were initially set at 2200 µmol m−2 s−1 indicated photosynthetic photon flux density (PPFD), A was allowed to stabilize, data was recorded, indicated PPFD level was reduced by 200 µmol m−2 s−1, and the process was repeated to a level of 200 µmol m−2 s−1. At GS6 all data were unaffected by N-fertility, hybrids, or years. Data on Ci at GS6 indicated A declines faster with decreasing PPFD than gs. Intrinsic water use efficiency (IWUE) data supports prior research showing stomata function more to regulate water loss and only marginally limit A. Nitrogen fertility was null on A and stomatal functions and minimal on yield; thus no attempt was made to correlate yield with these data.